Jose Antonio Encinas and the University Reform of Lima in 1931 - Machaca Arque, Néstor Jorge (2019)
The research is intended to highlight the leading role of José Antonio Encinas, one of the main educators of Peru in the 20th century, who exerted a remarkable influence on Peruvian education. This study focuses between the years 1931 and 1932. During this period in which events occurred that convulcionaron the Peruvian society, Rector Encinas implemented the University reform of 1931. The same that would be truncated in 1932 when the Universidad Nacional Mayor de San Marcos was closed.